Isolation of high-purity myenteric plexus from adult human and mouse gastrointestinal tract - Grundmann, David; Schäfer, Karl Herbert (Scientific reports, 2015)
The enteric nervous system (ENS) orchestrates a broad range of important gastrointestinal functions such as intestinal motility and gastric secretion. The ENS can be affected by environmental factors, diet and disease. Changes due to these alterations are often hard to evaluate in detail when whole gut samples are used. Analyses based on pure ENS tissue can more effectively reflect the ongoing changes during pathological processes. Here, we present an optimized approach for the isolation of pure myenteric plexus (MP) from adult mouse and human. To do so, muscle tissue was individually digested with a purified collagenase. After incubation and a gentle mechanical disruption step, MP networks could be collected with anatomical integrity. These tissues could be stored and used either for immediate genomic, proteomic or in vitro approaches, and enteric neurospheres could be generated and differentiated. In a pilot experiment, the influence of bacterial lipopolysaccharide on human MP was analyzed using 2-dimensional gel electrophoresis. The method also allows investigation of factors that are secreted by myenteric tissue in vitro. The isolation of pure MP in large amounts allows new analytical approaches that can provide a new perspective in evaluating changes of the ENS in experimental models, human disease and aging.
Gesehen am 04.10.2017